A Learner's Guide to the Old Church Slavic Language. Teil 1: Grammar with Exercises Teil 1: Grammar with Exercises - Regier, Philip J. (Slavistische Beitraege, 1977)
This book ist intended as a guide for those who wish to learn a language which is importand for comparative Slavik studies (in order to facilitate subsequent study of more than one of the Slavik languages, just as Latin facilitates study oft he Romance languages), for an understanding of the Church Slavik element of Russian (as important as the Latin element in English), or for comparative Indo-European studies. The approach taken ist hat of generative grammar, which provides for the most cohesive and precise formulation of the principles of a language, enabling the student to learn the language from the inside out.